2017
DOI: 10.15448/1980-6108.2017.2.26555
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho muscular isocinético dos ombros em atletas de rúgbi

Abstract: RESUMOOBJETIVOS: Verificar a existência de assimetrias dos músculos rotadores externos e internos entre os dois ombros, em atletas amadores de rúgbi do gênero masculino. MÉTODOS: Avaliações isocinéticas de atletas amadores do rúgbi masculino foram acessadas a partir do banco de dados do Instituto de Medicina do Esporte e Ciências Aplicadas ao Movimento Humano da Universidade de Caxias do Sul (IME-UCS). Foram incluídas as avaliações do ombro e excluídos os casos sem assinatura do Termo de Consentimento Livre e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Eight studies (Table 3) used isokinetic assessment with four different dynamometers in concentric 25,26 or concentric and eccentric modes 2732 to measure the maximal internal and external glenohumeral rotation torques at 60 °/s, 2528,32 120 °/s, 25 180 °/s, 26,31 or 240 °/s 2830,32 when the player was standing 29,30 or sitting, 2628,31,32 with the arm in a neutral position, 25 or abducted at 30°, 2832 60°, 26 or 90° 27 in the frontal 31 or scapular plane. 2630,32 Four studies provided mean values for dominant and nondominant sides, 2628,32 three studies provided for right and left sides, 2931 and one study combined the mean values for the two sides.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies (Table 3) used isokinetic assessment with four different dynamometers in concentric 25,26 or concentric and eccentric modes 2732 to measure the maximal internal and external glenohumeral rotation torques at 60 °/s, 2528,32 120 °/s, 25 180 °/s, 26,31 or 240 °/s 2830,32 when the player was standing 29,30 or sitting, 2628,31,32 with the arm in a neutral position, 25 or abducted at 30°, 2832 60°, 26 or 90° 27 in the frontal 31 or scapular plane. 2630,32 Four studies provided mean values for dominant and nondominant sides, 2628,32 three studies provided for right and left sides, 2931 and one study combined the mean values for the two sides.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (Table 3) used isokinetic assessment with four different dynamometers in concentric 25,26 or concentric and eccentric modes 2732 to measure the maximal internal and external glenohumeral rotation torques at 60 °/s, 2528,32 120 °/s, 25 180 °/s, 26,31 or 240 °/s 2830,32 when the player was standing 29,30 or sitting, 2628,31,32 with the arm in a neutral position, 25 or abducted at 30°, 2832 60°, 26 or 90° 27 in the frontal 31 or scapular plane. 2630,32 Four studies provided mean values for dominant and nondominant sides, 2628,32 three studies provided for right and left sides, 2931 and one study combined the mean values for the two sides. 25 The mean peak torque was the main outcome measure in all but one study; this measure was reported in Nm only in five studies 25,26,29,31 or in Nm and normalized by body mass in three studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations